COVID‐19 and U.S. Disputes Over Authority, 2020–2021: Implications for the Constructionist Analysis of Social Problems. Issue 4 (25th September 2022) - Best, Joel; Monahan, Brian
Abstract : COVID‐19 is very different from the cases typically studied by constructionist analysts of social problems: it emerged quickly, spread widely, and affected many aspects of social life. As such, it offers important opportunities to reconsider the constructionist model. We focus on three issues—metrics, masks, and vaccines—where COVID‐19 disputes about authority led to different alliances among several categories of claimsmakers. Our point is that COVID‐19 discourse seems far messier than most of the narratives presented by constructionist analysts, and we identify several lessons from this unusual contemporary case that might help us strengthen existing social problems theory.